ANALISIS PERBANDINGAN PENDEKATAN PENDIDIKAN MULTIKULTURAL DI INDONESIA DAN DUA NEGARA MAJU (AMERIKA SERIKAT, INGGRIS) - Irma Nur Agustin; Mokhamad Mahrus; Muslikh; Teguh Prasetyo; Alif Masruri Abdul Haq; Lukman Chakim (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
This study aims to compare the history, goals, and models of multicultural education in the United States, the United Kingdom, and Indonesia. The study focuses on analyzing the similarities and differences in multicultural education approaches in the three countries through qualitative research using a desk study method. Data sources were obtained from journals, books, policy documents, and the latest scientific publications (2019–2025), then analyzed using content analysis techniques to identify themes, concepts, and evolving patterns of approaches. The results show that multicultural education in the United States emerged as a response to racial discrimination in the 1960s, while in the United Kingdom it developed rapidly due to the large influx of immigration after World War II. In Indonesia, multicultural education has strengthened since the 1998 Reformation era as a strategy to address ethnic and religious diversity and potential social conflict. This study recommends that Indonesia needs to develop a multicultural education model based on an inclusive curriculum, a pedagogy of equality, and an empowering school culture to strengthen social cohesion and tolerance.